PENGARUH HARGA, LOKASI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM (Studi Kasus UMKM Kuliner Cisauk Corner Kecamatan Cisauk, Kabupaten Tangerang) - M. Deva Sutarno (2021)
The Effect of Price, Location, and Product Quality on Purchasing Decision SMEs Product (Case Study of Culinary SMEs "Cisauk Corner" in Cisauk Subdistrict, Tangerang Regency) By M. Deva Sutarno Abstract The Cisauk Corner Culinary MSME area is a place to eat where many individual Culinary MSME actors set up businesses and sell in that location. and provides a wide selection of food menus so that buyers can choose according to their taste. This study aims to determine what variables affect the price, location, and product quality variables on purchasing decisions. The population of this study is consumers who have made purchases at the Culinary MSMEs in Cisauk Corner and are domiciled in Cisauk Sub-district, Tangerang Regency. The number of samples is 75 respondents by using non-probability sampling technique of sampling with accidental sampling method. Data collection is done by distributing online questionnaires in the form of google forms. The analytical technique used is descriptive analysis using Patrial Least Square (PLS). The results obtained are: (1) Price has no significant effect on Purchase Decisions with a path coefficient value of 0.176. (2) Location has no significant effect on purchasing decisions with a path coefficient value of 0.041. (3) Product quality has a significant effect on purchasing decisions with a path coefficient value of 0.584. And get an R-Square value of 0.541 or 54,1%. Keyword: Price, Location, Product Quality, and Purchasing Decisions